IMPLEMENTASI KEBIJAKAN SUNSHINE POLICY SEBAGAI BENTUK UPAYA KOREA SELATAN DALAM PROSES REUNIFIKASI DENGAN KOREA UTARA PADA MASA KEPEMIMPINAN KIM DAE JUNG TAHUN 1998 – 2002 - Anindita, Vinesha (Global and Policy Journal of International Relations, 2017)
ABSTRACTThe Sunshine Policy policy was the first policy to unite South Korea's and South Korea's diplomatic relations following the outbreak of the 1950 Korean War. From the time of Park Chung Hee's leadership to Kim Young Sam, it has not been able to create a policy that provides a resolution to the conflict on the Korean Peninsula. Kim Dae Jung with the Sunshine Policy policy provides a solutive policy in reconciliation and reunification efforts on the Korean Peninsula. The approach used in the implementation process of Sunshine Policy policy in this research is through 3 theoretical approaches are track one diplomacy, soft power, and foreign aid. Through these three approaches, the Sunshine Policy policy is considered to have been successfully implemented, namely from the response and proactive attitude of North Korea.Keywords: Sunshine Policy, strategic moves, track one diplomacy, soft power, foreign aidDOI : https://doi.org/10.33005/jgp.v5i01.1904